RANCANG BANGUN APLIKASI ADVISOR AND MONITORING SERVICE PADA AUTO2000 PERMATA HIJAU BERBASIS ANDROID - Darmuli, Andri; Fauziyah, Fauziyah; Whendasmoro, Raditya Galih (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Service advisor and monitoring is an activity of providing advice and monitoring related to vehicle service and repair. Service Advisor is useful for providing information and advice to customers regarding service at Auto2000. The purpose of this research is to solve problems where customers and service advisors can connect online to provide information and advice. In making the advisor and monitoring service system, the method used is the Software Development Life Cycle (SDLC). The SDLC method has 6 steps: (1) Planning, (2) Analysis, (3) Design, (4) Implementation, (5) Testing, (6) Maintenance. The Auto2000 Advisor and Monitoring application is designed using diagram modeling, namely the Unified Modeling Language (UML), such as Use Case Diagram, Activity Diagram and Class Diagram. While testing is done using the MC Call criteria. From the research that has been done, the advisor and monitoring system makes it easier to provide advice or input to customers on service and service monitoring in monitoring.